Olfactory specificity regulates lipid metabolism through neuroendocrine signaling in Caenorhabditis elegans - Ayse Sena Mutlu (Nature Portfolio, 2020)
Olfaction is a key sensory modality with high diversity and olfactory defects has been associated with metabolic and neurodegenerative disorders. Here, the authors discovered that specific olfactory inputs actively regulate lipid metabolism in a dynamic and reversible manner.